Nanoparticles : Optical and Ultrasound Characterization. - Brodsky, Anatol M. (De Gruyter, 2011)
Many objects of physical, biological, and industrial interest include randomly distributed nanoscale nonuniformities, e.g., nanoparticles. Their characterization online in dynamic industrial processes and in situ in biological systems faces serious practical challenges when the rapid formation and distribution of nanoparticles takes place. This book discusses optical methods - the best tools for nanoparticle monitoring, as they are fast, noninvasive, and provide a broad range of information in real time - and their application in molecular biology and nanotechnology.